Evolução do estado nutricional de escolares de Itaqui-RS: reflexos da transição nutricional em uma década - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The nutritional transition in Brazil has led to a substantial rise in cases of overweight and obesity among children and adolescents, reflecting shifts in eating habits and lifestyles within the population. Objective: To assess the nutritional status of schoolchildren in the municipality of Itaqui, Rio Grande do Sul, and to compare this with SISVAN data from 2014 and 2024. Methods: This descriptive observational study involved a comparative analysis of data collected and data from the SISVAN database at two time points (2014 and 2024) in independent samples of schoolchildren from the public education system in the municipality of Itaqui, Rio Grande do Sul. Anthropometric data were collected from 634 schoolchildren in 2024 and compared with secondary data extracted from the SISVAN database. Nutritional assessment was based on height-for-age (H/A) and BMI-for-age (BMI/A) according to World Health Organization (WHO) criteria. Results: An increase in the prevalence of obesity (7.1%) and severe obesity (2.3%) was observed among the evaluated children, particularly among overweight adolescents (12.5%), as well as a reduction in the prevalence of stunting (2.5%) among children and 1.9% among adolescents. SISVAN data coverage also increased in 2024, reaching approximately 1,000 individuals, which is possibly associated with the strengthening of intersectoral actions in the region. Conclusion: Despite the improvement in height indicators, the prevalence of overweight among schoolchildren constitutes a growing public health challenge that requires prevention strategies and the strengthening of public policies in the school environment.
Evolution of the nutritional status of schoolchildren in Itaqui-RS: reflections of the nutritional transition in a decade
Keywords: Estado nutricional; Escolares; Obesidade infantil; Vigilância nutricional; Políticas públicas; Nutritional status; Schoolchildren; Childhood obesity; Nutritional surveillance; Public policies; CIENCIAS DA SAUDE